Effects of pepper – peanut intercropping systems on processed chili yield and rhizospheric soil microecological environment - Wang, Jingjing; Gai, Xiapu; Wang, Youping; Chang, Peipei; Li, Tengfei; Zhang, Shaoli; Zhang, Hongyong; Li, Hongbo; Zhang, Zikun (Frontiers in Plant Science, 2025)
IntroductionThis study investigated the effects of pepper - peanut intercropping patterns on the rhizosphere soil microenvironment and yield of processing chili.MethodsUsing the processing chili varieties “Beike 802” and “Dehong 1” as test materials, treatments included monoculture (BK, DH) and peanut intercropping (BKIM, DHIM). The dry matter accumulation, agronomic traits, photosynthetic parameters, soil nutrients, enzyme activities and microbial community changes were analyzed by split plot experiment design.Results and discussionThe results demonstrated that intercropping significantly enhanced dry matter accumulation in pepper plants (the dry matter accumulation of pepper was increased by 25.25% in BKIM compared with BK in full fruit period, p<0.05). Yield per 667 m2 increased by 9.12% to 15.01%, and the number of fruits per plant rose by 10.14% to 13.39%, with differences being statistically significant (p < 0.05). Photosynthetic parameters—including net photosynthetic rate (Pn), stomatal conductance (Gs), and transpiration rate (Tr)—were significantly higher under intercropping at the full fruit stage (p < 0.05), while intercellular CO2 concentration also increased synchronously. Soil nutrient analysis revealed that intercropping significantly increased organic matter (e.g., DHIM reached 19.92 g kg-¹) and available phosphorus content but reduced available potassium levels (p < 0.05). Microbial community analysis indicated a significant rise in bacterial and fungal operational taxonomic units (OTUs) under intercropping (e.g., bacterial OTUs in BKIM increased by 91.26% compared to BK, p < 0.01). The abundance of key beneficial taxa such as Proteobacteria and Chytridiomycota was enhanced, and soil microbial diversity indices (ACE and Chao1) were markedly higher in intercropped treatments (p < 0.05).ConclusionIn summary, pepper - peanut intercropping significantly promoted pepper yield by optimizing photosynthetic efficiency and improving soil microecology, providing a theoretical basis for alleviating continuous cropping obstacles.